My Say: Islam and youth empowerment in Malaysia Madani - Bakar, Osman (The Edge Communications Sdn. Bhd., 2023)
The contemporary challenges to youth life and thought are numerous. In the development of each individual, life and thought are found to be very closely intertwined. Thought is supposed to influence and shape life, while life is expected to enrich thought. This is generally the case in theory, especially for adult life and thought. In practice, however, the intertwining pattern between life and thought is much more complex, and it varies from individual to individual.